2016
DOI: 10.1016/j.gemrev.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of strategic management research on M&As: Citations, co-citations, and topics

Abstract: Merger and acquisitions (M&As) strategies have been growingly deployed by firms for their domestic and international expansion, to redefine their business scope or take advantage of emerging opportunities. In this paper we conduct a bibliometric study of the extant strategy research on M&As, assessed by the articles published in the main journal for strategic management studies over the period 1984-2010. Results reveal the highest impact works (articles and books), the intellectual ties among authors and theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
0
6
0
1
Order By: Relevance
“…Zarządzanie strategiczne obejmuje zrozumienie pozycji organizacji, wybory na przyszłość oraz zarządzanie strategią w praktyce (Omalaja, Eruola, 2011). W badaniu strategii wykorzystywanych jest kilka perspektyw pojęciowych, takich jak: perspektywa kosztów, szkoła zasobów kompetencji, organizacyjne uczenie się, teoria agencji oraz koncepcje finansowe związane z organizacją (Ferreira, dos Reis, Pinto, 2016). Od właściwego zrozumienia idei strategii zależy powodzenie tej, która zostanie obrana.…”
Section: Przegląd Literatury 21 Zarządzanie Strategiczneunclassified
See 1 more Smart Citation
“…Zarządzanie strategiczne obejmuje zrozumienie pozycji organizacji, wybory na przyszłość oraz zarządzanie strategią w praktyce (Omalaja, Eruola, 2011). W badaniu strategii wykorzystywanych jest kilka perspektyw pojęciowych, takich jak: perspektywa kosztów, szkoła zasobów kompetencji, organizacyjne uczenie się, teoria agencji oraz koncepcje finansowe związane z organizacją (Ferreira, dos Reis, Pinto, 2016). Od właściwego zrozumienia idei strategii zależy powodzenie tej, która zostanie obrana.…”
Section: Przegląd Literatury 21 Zarządzanie Strategiczneunclassified
“…Strategic management involves understanding an organization's strategic position, strategic choices for the future and managing strategy in action (Omalaja, Eruola, 2011). Strategy research uses several conceptual lenses: a cost view, a resource-based view, organizational learning, agency theory and financial concepts related to organizations (Ferreira, dos Reis, Pinto, 2016). A good understanding of the concept of strategy will determine the success of one to be drawn up.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that strategy accounts for 11 percent of research disciplines used in the SLR is supported by other research. The bibliometric study from Ferreira et al (2016) into strategy research on M&A from 1984 to 2010 found M&A research is scarce (under 6 percent of total articles published in Strategic Management Journal ) and has not followed the growth of M&A as a strategy in practice. Evidence suggests scant research linking stakeholders and M&A coming from the strategy discipline.…”
Section: Insights and Critiquementioning
confidence: 99%
“…First, the resource-based view (RBV) and value-rarityimitability-organization (VRIO) method encouraged users to evaluate resources relative to competitors (Knott 2015) but not to business partners. RBV still demonstrates "reasonably lacking an understanding of how firms' resources and capabilities truly play a role on M&A" (Ferreira et al 2016), or other types of coopetitive strategies such as strategic alliances and cooperative arrangement (McGee et al 1995;Child et al 2019). That is because the RBV has "a tendency to elicit static and inward-looking descriptions that are insufficiently geared to future-focused decisions" (Lockett et al 2009;Knott 2015Knott , p. 1816.…”
Section: Introductionmentioning
confidence: 99%